Integrating policy agendas for sustainable innovation: a quadruple helix approach to the European Green Deal and sustainability transitions - Popper Monika; Popper Rafael; Rapetti Carina Alejandra; Pique Josep Miquel (Engineering Management in Production and Services)
This paper explores the integration of DIY (Do-It-Yourself) and crowdsourcing-driven innovation management with top-down policy frameworks to advance the European Green Deal and sustainability transitions. Drawing on the CASI (Common Framework for the Assessment and Management of Sustainable Innovation) project, it examines how CASI-F and its CASIPEDIA platform — a repository of over 700 sustainable innovation initiatives — can bridge local and global sustainability goals. Using a quadruple helix approach, the study highlights the role of innovation ecosystems in driving systemic change through the alignment of technological, economic, social, and environmental objectives. The paper compares the CASI SI agendas with the European Green Deal and sustainability transition agendas, identifying synergies, gaps, and opportunities for further alignment. Foresight is emphasised as a crucial tool to ensure innovation strategies remain adaptable, future-oriented, and resilient to emerging challenges. The findings underscore the importance of integrating grassroots innovations into broader policy frameworks to enhance sustainability transitions. Lastly, the paper recommends strengthening the Green Deal by fostering innovations from diverse actors, including those from the quadruple helix, and promoting the application of SMART foresight processes.